Treatment of delayed rupture of the left ventricle after mitral valve replacement - Gomes,Walter J. (2002)
Rupture of the left ventricle following mitral valve replacement is a catastrophic complication with deadly consequences. We report here the case of a 75-year-old man who underwent elective mitral valve replacement for severe mitral regurgitation. Delayed type 1 rupture of the left ventricle developed 3 hours postoperatively in the intensive care unit. A salvaging maneuver was used, which gained time, allowing reoperation and successful intraventricular repair.